2007
DOI: 10.1186/1742-4690-4-85
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with HIV-1, HIV-2, and HTLV-I single and dual infections in a middle-aged and older population in Guinea-Bissau

Abstract: Background: In Guinea-Bissau HIV-1, HIV-2, and HTLV-I are prevalent in the general population. The natural history of HIV/HTLV-I single and dual infections has not been fully elucidated in this population. Previous studies have shown that combinations of these infections are more common in older women than in men. The present study compares mortality associated with HIV-1, HIV-2, and HTLV-I single and dual infections in individuals over 35 years of age within an urban communitybased cohort in Guinea-Bissau.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 54 publications
1
45
2
Order By: Relevance
“…If this is true, HIV-D-infected individuals would be expected to have a lower mortality rate than HIV-1-mono-infected individuals [21]. However, several large comparative studies from West Africa did not report reduced mortality rates among the HIV-Dinfected individuals [13,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…If this is true, HIV-D-infected individuals would be expected to have a lower mortality rate than HIV-1-mono-infected individuals [21]. However, several large comparative studies from West Africa did not report reduced mortality rates among the HIV-Dinfected individuals [13,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate in HIV-2-infected patients is at least twice that of uninfected individuals (26). Nonetheless, the majority of HIV-2-infected individuals survive as elite controllers (17).…”
mentioning
confidence: 99%
“…Dual infection with HIV-1 and HIV-2 occurs mainly in West Africa, where the two viruses cocirculate. Several papers have indicated that dually infected patients have a disease course similar to that of patients infected with HIV-1 alone (21,52). The presence of HIV-2 in individuals dually infected with HIV-1 and HIV-2 complicates the treatment of these patients (53).…”
mentioning
confidence: 99%